An underexplored pathway to life satisfaction: The development and validation of the synchronicity awareness and meaning-detecting scale - Russo-Netzer, Pninit; Icekson, Tamar (Frontiers in Psychology, 2023)
Introduction Synchronicity refers to the psychological process of meaningful coincidences. The present study aimed to build and expand upon a model of synchronicity awareness and meaning-detecting (REM)—receptiveness (R) as a precondition for an exceptional encounter (E) triggering emotions and meaning-detecting (M)—by assessing the prevalence of the phenomenon and its associations with well-being. Methods and Results Results from two studies reported here employing adult community samples (N = 198 and N = 440) demonstrate coherent, replicable structure and good internal reliability for a 35-item, two-factor Synchronicity Awareness and Meaning-Detecting (SAMD) Scale. Synchronicity awareness (SA) and meaning-detecting (MD) scores were significantly associated with some of the Big-5 personality dimensions and tolerance for ambiguity, as well as with search for and presence of meaning. Furthermore, process mediation models showed: (a) synchronicity awareness mediated the relationship between search for meaning and meaning-detecting, and (b) optimism and presence of meaning in life partly mediated the relationship between meaning-detecting and life satisfaction. Discussion The findings suggest the importance of synchronicity experiences and hold important conceptual and practical implications for understanding processes of meaning making from unexpected events and their potential contribution to individuals’ well-being.